2022
DOI: 10.1186/s12903-022-02337-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between migration and oral health-related quality of life: results from a nationally representative online survey

Abstract: Purpose To analyze the link between individuals with and without migration background and oral health-related quality of life (also stratified by sex). Methods Data in this cross-sectional study were taken from a nationally representative survey (n = 3075, August/September 2021). The Oral Health Impact Profile (OHIP-G5) was used to measure oral health-related quality of life. Two-part models were calculated, adjusting for various covariates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…9 Better health-related behaviors and routine dental attendance have a protective effect on OHRQoL. 10 At present, the association between sociodemographic factors, clinical dental conditions, oral health behaviors, and OHRQoL has been investigated in adolescents, the elderly, pregnant women, and adult populations, [11][12][13][14] while the research on OHRQoL and compliance of oral health behaviors of dental patients in China are sparse, who have a high prevalence of oral diseases, deserve more attention. According to the Fourth National Oral Health Survey (2015-2016) in mainland China, 15 a large proportion (more than 52.8%) of Chinese adults have periodontal disease, and the severity of periodontal disease was positively associated with age.…”
Section: Introductionmentioning
confidence: 99%
“…9 Better health-related behaviors and routine dental attendance have a protective effect on OHRQoL. 10 At present, the association between sociodemographic factors, clinical dental conditions, oral health behaviors, and OHRQoL has been investigated in adolescents, the elderly, pregnant women, and adult populations, [11][12][13][14] while the research on OHRQoL and compliance of oral health behaviors of dental patients in China are sparse, who have a high prevalence of oral diseases, deserve more attention. According to the Fourth National Oral Health Survey (2015-2016) in mainland China, 15 a large proportion (more than 52.8%) of Chinese adults have periodontal disease, and the severity of periodontal disease was positively associated with age.…”
Section: Introductionmentioning
confidence: 99%
“…Segregation might facilitate lower attendance to regular check-ups with worsened dental health and dissatisfaction with teeth as consequence. In cross-sectional study performed in Germany found those having immigrated indeed had a lower oral health-related quality of life (243).…”
Section: Resultsmentioning
confidence: 96%
“…Пропаганда знань про догляд за порожниною рота та формування відповідних звичок і безпечного харчування є необхідною із раннього віку для формування відповідних звичок у дорослому віці. Для подолання негативного впливу низького рівня стоматологічного здоров'я у дитячого населення наявна актуальна потреба в дослідженні та розумінні детермінант, які призводять до нерівності такого здоров'я [6][7][8][9][10].…”
Section: двнз «ужгородський національний університет» ужгород українаunclassified